Comparative Advantage and Export Performance of Indonesia and Vietnam Coffee to the US Market during 2001-2019 - Dian Galuh Pratita; Rahmat Budiarto (Department of Agribusiness, Faculty of Agriculture, Universitas Trunojoyo Madura, Indonesi, 2021)
Coffee as a strategic commodity in the world opens up opportunities for various producing countries including Indonesia and Vietnam. Both countries have a significant role to supply the US market as the main export destination. This study aims to evaluate comparative advantage and export performance of Indonesian and Vietnamese coffee. Quantitative method has been used by calculating the Revealed Comparative Advantage (RCA), Export Competitiveness Index (ECI), and Export Product Dynamic (EPD) using secondary data from 2001-2019. In term of RCA, both Indonesia and Vietnam have a comparative advantage in US. Indonesia’s RCA valuewas lower than Vietnam’sones, i.e., 5.52 8.57. This result was caused by the lower Indonesia’s export performance rather than Vietnam’s ones. The ECI of both countries were dynamic but tended to decrease in international market.In term of EPD, Indonesia and Vietnam were both in the rising star position that indicated strong capability of both countries in supplying coffee to the US market. Therefore, both countries shared a similar big opportunity to increase their coffee export quantities.